Effect of aerosolized antipseudomonals on Pseudomonas positivity and bronchiolitis obliterans syndrome after lung transplantation. Issue 3 (17th April 2017) - Moore, Cody A.; Pilewski, Joseph M.; Venkataramanan, Raman; Robinson, Keven M.; Morrell, Matthew R.; Wisniewski, Stephen R.; Zeevi, Adriana; McDyer, John F.; Ensor, Christopher R.
Abstract: Purpose: To describe the effects of aerosolized antipseudomonals (AAPs) on Pseudomonas (PS) culture positivity, bronchiolitis obliterans syndrome (BOS), and acute cellular rejection (ACR) in lung transplant recipients (LTRs). Methods: Single‐center, retrospective cohort study was performed of adult LTRs treated with either AAP for ≥28 days vs no AAP therapy or AAP therapy <28 days, indexed to a matched median date post lung transplantation (LT). Primary outcome was freedom from PS positivity by positive bronchoalveolar lavage or bronchial wash at 1 year. Secondary outcomes were freedom from BOS or BOS progression and ACR burden (defined by the novel composite rejection standardized score. Normality was assessed, and univariate and multivariate parametric and non‐parametric statistical tests were used to assess baseline characteristics and outcomes, where appropriate. Freedom from events was compared using the Kaplan‐Meier method with log‐rank conversion and risk was assigned using multivariable Cox proportional hazards (PH) modeling. Results: In total, 293 LTRs (105 with AAP, 188 with no AAP) were included. Median ages in AAP and control cohorts were 51 (30‐63) and 62 (54‐67) years ( P <.01). Median AAP duration was 198 (interquartile range 94‐395) days. Time to median positive PS culture was similar between AAP (median 1.02 [95% confidence interval CI 0.74‐1.22] years) and control (median 0.96 [95% CI 0.72‐1.21] years). Log‐rank test for time‐to‐PS positivity was similar for both groups (log‐rank P =.26). Incidence of PS culture positivity at 1 year was similar in APP vs controls (59.0% vs 54.8%, P =.48). In the non‐cystic fibrosis (CF) subgroup, AAP use was protective against PS recurrence on univariate Cox PH model (hazard ratio [HR] 0.55, 95% CI 0.38‐0.83) and on multivariate Cox PH adjusting for age and induction (HR 0.56, 95% CI 0.38‐0.83). Incidence of new‐onset BOS or BOS progression in APP vs control at 1 (17.1% vs 14.9%, P =.61) and 3 (38.1% vs 37.8%, P =.96) years was similar. CRSS was similar in APP vs control group at 1 year (0.42 vs 0.33, P =.41). Conclusion: AAP use was not associated with less PS positivity, BOS, or ACR in all LTRs. In the non‐CF subgroup analysis, treatment with AAPS was associated with protection against recurrent PS. Limitations include retrospective design, heterogeneous AAP therapy among LTRs, and potential convenience sampling of LTRs receiving AAPs for >28 days at our center. Larger assessments and better controlled analyses are required to further define efficacy of AAPs after LT.